La desproporcionalidad de la prescripción en los delitos contra la vida e integridad sexual, en comparación con la imprescriptibilidad de los delitos contra la administración pública - Garcés Paredes, Luis Aníbal (2017)
This work responds to the following questions: Is it proportional that the crimes against the efficient public administration are imprescriptible while serious illicit and that have a greater impact, such as those that go against sexual life and integrity do not have this special protection? And if it is not the answer, what is a proposal to achieve a fair legal framework? To answer these questions, in the first chapter an explanation of what is the prescription and its exception was made: the imprescriptibility, the method used is the exegetical applied to the description of the crimes under study and the justification of the importance of the Indicators of necessity of the character of imprescriptible. In the second chapter the first question is answered. It is based on 3 parameters of imprescriptibility, which are: the protected legal right, the damage caused to it, when it is affected and the penalty assigned to each crime; the chapter closes with the inclusion of a comparative analysis. In the third chapter, the second question is answered. Proposals for reform are made that allow compliance with the principle of proportionality, in terms of the treatment of the prescription in the offenses that are analyzed, in addition to the achievements obtained from conducting the trial.